Association of aspirin therapy with risk of hepatocellular carcinoma: A systematic review and dose-response analysis of cohort studies with 2.5 million participants. (January 2020) - Wang, Shuijing; Yu, Yan; Ryan, Paul M.; Dang, Minyan; Clark, Cain; Kontogiannis, Vasileios; Rahmani, Jamal; Varkaneh, Hamed Kord; Salehisahlabadi, Ammar; Day, Andrew S.; Zhang, Yong
Graphical abstract: Abstract: Although aspirin is commonly used for the prevention of cardiovascular disease, evidence from research has shown that these beneficial effects might extend to hepatocellular carcinoma (HCC). This dose-response analysis was performed to investigate the association between aspirin use and risk of HCC. A systematic search was conducted in MEDLINE/PubMed, SCOPUS, Cochrane, and Web of Science databases from inception up to 29th October 2019. DerSimonian and Laird Random-effects model was used to estimate pooled hazard ratios (HRs) from included studies. Overall, eight studies containing 2, 604, 319 participants evaluating the association between aspirin use and risk of HCC were uncovered and included in the present meta-analysis. Pooled results of included studies showed a significant reduction in risk of HCC in participants who used aspirin (HR 0.59, 95 % CI 0.47-0.75, Pheterogeneity = 0.001, I 2 = 90 %). In total, 13, 636 cases of HCC detected during the follow-up period of these studies. Furthermore, linear dose-response model showed an significant inverse association between aspirin dose and risk of HCC (exp (b) = 0.994, p < 0.001), while non-linear dose-response analysis revealed an even more robust association (Coef1 =-0.008, p1 = 0.04, Coef2 = 0.033, p2 = 0.13). This systematic review and dose-response analysis identified significant inverse relation between aspirin and risk of HCC using both linear and non-linear models.